(untitled) (Research, Society and Development, 2022)
Objectives: to characterize the scientific productions raised considering the variables: author, year, title, objectives, type of study and results; discover the care strategies carried out by nurses during the COVID-19 pandemic; Discuss the difficulties encountered by nurses in the care provided during the COVID-19 pandemic. Methodology: This is an integrative review study, carried out in November 2021, which covers the electronic databases used for Latin American and Caribbean Literature in Health Sciences, Nursing Data Base and the Virtual Library Scientific Electronic Library On-line. The searches were carried out using the Descriptors in Health Sciences (DeCS) of the Regional Library of Medicine (Bireme): Nursing Care, Nursing, Pandemics, as well as the uncontrolled describer: coronavirus infections, with the help of the Boolean operator “AND” . Results: We studied foram selected 10 articles, published between 2020 and 2021, which were discussed for purposes of analysis, whose results were grouped and discussed in thematic categories: The care strategies carried out by nurses during the COVID-19 pandemic and difficulties encountered Nursing hairs during the COVID-19 pandemic. Conclusion: Given the exposure, it was possible to place in emphasis the main strategies of nursing professionals and their strong contribution to the management of patients affected by COVID-19 care. In addition, the research in this area will be able to contribute to the assistance of individuals who will contract the SARS-CoV-2 virus. The limitations of the study are consistent with the scarcity of approaches regarding this theme, because it is still recent and lacks research.